Hydrogen transport within graphene multilayers by means of flexural phonons. (20th February 2015) - Camiola, Vito Dario; Farchioni, Riccardo; Pellegrini, Vittorio; Tozzini, Valentina
Abstract: Graphene sustains transverse out-of-plane mechanical vibrations (flexural phonons). At the nanometer scale, these appear as traveling ripples, or cavities, if excited in counter-phase in alternate multilayers. In this work we explore by means of classical molecular dynamics simulations the possibility of using these moving nano-cavities to actively transport hydrogen. We find that the gas can be efficiently transported for hundreds of nanometers in the wave propagation direction, before the phonons damp down. Therefore, this effect could be used to move and pump gases through multilayers graphene based frameworks.